Management Strategy of Museum Subang For Addressing Challenges In Public Services At The Museum - Muhamad Abdu (Socius: Jurnal Penelitian Ilmu-Ilmu Sosial, 2026)
This study aims to identify the procedures, challenges, and strategies for addressing challenges related to museum management in public services at the Museum Subang. This study employs a qualitative approach using the case study method at the Museum Subang. Data collection techniques included observation, interviews, and document review, with data analysis conducted through data reduction, data presentation, and drawing conclusions, as well as through an ASOCA (Ability, Strength, Opportunities, Culture, and Agility) analysis to determine the strategies to be implemented. The management of the Museum Subang in terms of public services is in accordance with existing standard operating procedures (SOPs); however, the museum’s role in providing public services has not yet been fully optimized. Some of the museum’s programs involve students more than the general public. Challenges faced in providing services at the Museum Subang include the quality of the museum’s human resources, the lack of interactive exhibits, the need for digitization and the expansion of museum facilities, as well as the need for programs and promotional efforts to increase public participation in museums.